KINERJA BELUM OPTIMAL? ANALISIS KOMPENSASI DAN DISIPLIN KERJA PADA CV XYZ SURABAYA - Lutfia Raihany; Sulastri Irbayuni (STKIP Persada Khatulistiwa Sintang, 2026)
This study is motivated by the decline in employee performance at CV XYZ Surabaya, as reflected in sales targets that have not been consistently achieved in recent periods. This situation indicates issues in human resource management that require evaluation. The study examines the influence of managerial factors, particularly compensation and work discipline, on employee performance as an effort to improve the effectiveness of human resource management within the company. Compensation is viewed as a form of appreciation for employees’ contributions, while work discipline reflects employees’ compliance with company regulations and operational standards. The objective of this research is to empirically analyze the effect of compensation and work discipline on employee performance at CV XYZ Surabaya. The study uses a quantitative approach with Partial Least Squares (PLS) analysis, involving 60 respondents from the marketing and warehouse divisions. The results show that compensation contributes to employee performance, with overtime pay providing a considerable contribution. Work discipline also contributes to performance, particularly through adherence to company rules and punctuality. These findings highlight that fair compensation and consistent discipline play an important role in enhancing employee performance.